AN ANALYSIS OF LOGICAL FALLACY ON JOKO WIDODO’S ARGUMENTS DURING 2019 INDONESIA PRESIDENTIAL DEBATE - Jaka Satria Warman; Hamzah Hamzah (English Language and Literature, 2019)
This research aimed at finding the types of logical fallacies on Indonesia presidential debates made particularly by one of the presidential candidates, Joko Widodo, during the 2019 Indonesia presidential debates. The theory of fallacy classification by Damer (2009) which introduces five categories and sixty types of fallacies was employed in this research. Of all the sixty types, only twelve of which were found. The results show that, first, fallacies that violate the rebuttal criterion became the most dominantly occurred category with the occurrence of more than a half number of all occurrences and with five types out of twelve types. Second, abusive ad hominem was the most dominant type made by Jokowi with the frequency of 21.73% and followed by the fallacy of red herring and false alternatives with the same frequency of 17.39.